Review of the aphid genus Aspidophorodon Verma, 1967 with descriptions of three new species from China (Hemiptera: Aphididae: Aphidinae) - Chen, Jing; Zhang, Bin; Zhu, Xichao; Jiang, Liyun; Qiao, Gexia (Zootaxa, 2015)
The aphid genus Aspidophorodon Verma, 1967 is reviewed, with descriptions of three new species from China, namely Aspidophorodon (Aspidophorodon) cornuatus Qiao sp. nov., Aspidophorodon (Aspidophorodon) musaicus Qiao sp. nov., and Aspidophorodon (Aspidophorodon) obtusus Qiao sp. nov.. Aspidophorodon sinisalicis Zhang, 1980 and Trichosiphonaphis lijiangensis Zhang, Zhong & Zhang, 1992 are considered as junior synonyms of Aspidophorodon (Aspidophorodon) salicis Miyazaki, 1971, syn. nov.. The Chinese endemic genus Margituberculatus Zhang, Zhong & Zhang, 1992 is proposed as a junior synonym of Aspidophorodon (Eoessigia) David, Rajasingh & Narayanan, 1972, syn. nov., this subgenus is thereby recorded from China for the first time and Margituberculatus longituberculatus Zhang, Zhong & Zhang, 1992 is referred to as Aspidophorodon (Eoessigia) longituberculatus (Zhang, Zhong & Zhang, 1992) comb. nov.. A generic diagnosis and keys to Aspidophorodon species are given. Molecular evidence to support the validity of new species and their subgeneric affiliation is also provided.